Analysis of the self-compassion and cognitive flexibility with marital compatibility in parents of children with autism spectrum disorder - Shahabi, Bahareh (Int J Dev Disabil, 2019)
Purpose: Parents of children with autism spectrum disorder (ASD) face many problems in their marital lives. Autism is a developmental disorder, emerging during childhood that affects development across various domains. Studies suggest that autism prevalence rates are increasing, and research shows that parents of children with ASD frequently experience high levels of parenting stress. Marital compatibility is fulfilled when couples have the sense of satisfaction and contentment from each other. This study was done to analyze self-compassion and cognitive flexibility in relation with marital compatibility in parents having children with ASD. Methods: A sample size with 100 married couples, who referred to autism centers, was selected after clinical interviews. The research tools included structural clinical interview (DSM SCID), self-compassion scales questionnaire, cognitive flexibility inventory questionnaire, and marital compatibility test questionnaire, which were completed by the participants. Results: The research is a correlational descriptive study. Data analysis was done by the path analysis method. The findings showed that there was a significant relation between self-compassion, cognitive flexibility, and marital compatibility. Conclusions: In this study, it could be concluded that compassion via flexibility can have indirect positive effects on marital compatibility as two features of self-compassion and cognitive flexibility can help parents of children with ASD to be more compatible and flexible in their marital lives.